2017
DOI: 10.2147/ijn.s133708
|View full text |Cite
|
Sign up to set email alerts
|

Ravuconazole self-emulsifying delivery system: in vitro activity against <em>Trypanosoma cruzi</em> amastigotes and in vivo toxicity

Abstract: Self-emulsifying drug delivery systems (SEDDSs) are lipid-based anhydrous formulations composed of an isotropic mixture of oil, surfactant, and cosurfactants usually presented in gelatin capsules. Ravuconazole (Biopharmaceutics Classification System [BCS] Class II) is a poorly water-soluble drug, and a SEDDS type IIIA was designed to deliver it in a predissolved state, improving dissolution in gastrointestinal fluids. After emulsification, the droplets had mean hydrodynamic diameters <250 nm, zeta potential va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 55 publications
(64 reference statements)
0
17
0
5
Order By: Relevance
“…1,2 A number of alternative techniques including cyclodextrin complexation, 3 particle size reduction, 4 solid dispersions, 5 and lipid-based formulations 6 have been developed to overcome this problem. Among all the formulations, lipid-based formulations, especially self-emulsifying drug delivery systems (SEDDS) have received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A number of alternative techniques including cyclodextrin complexation, 3 particle size reduction, 4 solid dispersions, 5 and lipid-based formulations 6 have been developed to overcome this problem. Among all the formulations, lipid-based formulations, especially self-emulsifying drug delivery systems (SEDDS) have received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…El SCB se basa en estos dos factores para agrupar los principios activos en cuatro categorías principales [61], como se muestra en la figura 6. Inicialmente, los SEDDS surgieron como una alternativa ante la necesidad de superar los inconvenientes en la formulación de principios activos cuya baja solubilidad acuosa conlleva a una absorción gastrointestinal limitada por la disolución y a su vez en una biodisponibilidad baja y variable [62,63]. Generalmente, estos compuestos se encuentran categorizados como clase II o clase IV en el SCB [64,65].…”
Section: Principio Activounclassified
“…En ese sentido, los valores altos de HLB correspondientes a tensioactivos de naturaleza hidrofílica facilitan la disminución de la energía interfacial, lo que conduce a la formación de dispersiones más estables y de menor tamaño [63,107,111]. En general, el valor HLB para un tensioactivo hidrofílico se encuentra en el rango entre 12 y 18 [112].…”
Section: Tensioactivounclassified
See 1 more Smart Citation
“…Mechanistic study demonstrated that Labrasol can disrupt tight junctions at the molecular level, including the loss of junction integrity via changes in F-actin ring and redistribution of zonula occludens-1 (ZO-1), leading them to act as potential absorption enhancers of hydrophilic drugs. 54,55 Based on the results of the in vitro artificial intestinal membrane and Caco-2 cell monolayer permeability analyses, further experiments, including those on the in vivo oral absorption in rats and tumor growth suppression efficacy in mice, were carried out using HP-beta-CD/PMX/ DCK/P188-NE.…”
mentioning
confidence: 99%